The Approximation of a Modified Baskakov Operator - Ma Yingdian; Wang Weimeng (Journal of Mathematics)
Because of their simple form and high quality, linear arithmetical operators, particularly linear positive operators, are very popular. The number of in-depth studies on linear operator approximation is extensive, and the majority of the published material falls into four categories: types and structures of operators, approximation of operators, order of approximation and the converse theorem of operators, and operator saturation. The Baskakov operator will be transformed in the same way to explore its approximation characteristics as well as the approximation theorem and converse theorem.